A Feasible and Facile Method for the Anticounterfeiting of Down Fiber. (10th September 2021) - Jin, Qianpeng; Gao, Simeng; Xu, Yang
Abstract : In order to prevent counterfeiting of down fiber from consumers, rare earth fluorescent materials are developed in the field of material identification and anticounterfeiting. Herein, the development of verifiable down fiber based on infrared excitation-infrared emission was described. A novel method was approached to prepare security down fiber, which involved modification of down-conversion nanoparticles (DCNPs) by sulfonic groups and self-assembly onto down fiber through electrostatic force. DCNPs were successfully prepared from ytterbium-deposited NaYF4 nanoparticles using a complexation precipitation approach, in which the trivalent ytterbium ions served as the luminescent center. Sulfonic down-conversion nanoparticles (SO3 -SiO2 @DCNPs) were fabricated by the hydrolysis of 3-mercaptopropyl triethoxysilane (MPTES) and next oxidation to enhance the combination of the DCNPs with down fiber. The synthesis of DCNPs and SO3 -SiO2 @DCNPs and its pendant to down were confirmed by XRD, SEM, XPS, FT-IR, Zeta potential meter, and PL, which revealed the presence of DCNPs in the size average 86 nm. The obtained DCNPs and security down fiber were launching an invisible red-shifted emission of 930∼1080 nm (corresponding to the 2 F5/2 ⟶ 2 F7/2 transitions in Yb 3+ ). After washing, the infrared emission of security down fiber was evaluated and proved to be effective with fine results, which showed its potential application in the field of security.